2006
DOI: 10.1111/j.1600-0463.2006.apm_357.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to fluoroquinolones and beta‐lactams on the in vitro activity of other groups of antibiotics in Salmonella spp.

Abstract: After designing in vitro models of repeated exposure of Salmonella spp. to various beta-lactams and fluoroquinolones we studied the decrease in susceptibility to other antibiotic families of the mutants generated. There was a decrease in the susceptibility of all the mutants to tetracycline, cotrimoxazole and chloramphenicol. Mutants generated following exposure to fluoroquinolones showed reduced susceptibility to amoxicillin, amoxicillin/clavulanic acid, cefoxitin and cefuroxime, whereas mutants generated fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…This subcultured strain is considered to be resistant to amoxicillin (MIC > 8 μ g/mL) according to EUCAST's recommendations [ 22 ]. These results corroborate with those obtained by Cebrian et al [ 23 ] who showed that the in vitro exposure of Salmonella strains to amoxicillin induced a reduction in sensitivity to amoxicillin and other antibiotics. Furthermore, Qureshi et al [ 24 ] reported similar results for Helicobacter pylori strains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This subcultured strain is considered to be resistant to amoxicillin (MIC > 8 μ g/mL) according to EUCAST's recommendations [ 22 ]. These results corroborate with those obtained by Cebrian et al [ 23 ] who showed that the in vitro exposure of Salmonella strains to amoxicillin induced a reduction in sensitivity to amoxicillin and other antibiotics. Furthermore, Qureshi et al [ 24 ] reported similar results for Helicobacter pylori strains.…”
Section: Discussionsupporting
confidence: 92%
“…is subcultured strain is considered to be resistant to amoxicillin (MIC > 8 μg/mL) according to EUCAST's recommendations [22]. ese results corroborate with those obtained by Cebrian et al [23] who showed that the in vitro exposure of Salmonella strains to amoxicillin Our results also show that E. coli strain became less sensitive to tylosin and colistin, while these two antibiotics were not added to the subculture medium. e MICs of tylosin and colistin increased by 4-fold compared to the starting MICs.…”
Section: Discussionsupporting
confidence: 89%
“…They found that mutants generated after treatments with various FQs showed reduced susceptibility to a wide range of the antibiotics tested (seven different antibiotics). This was in contrast to mutants generated under treatment with β-lactams, which showed reduced susceptibility to fewer antibiotics (five antibiotics) [179]. Similarly, it has been shown that the treatment of methicillin-resistant St. aureus with sublethal FQ further enhances methicillin resistance [169].…”
Section: Treatment With Quinolones Increases Resistance To Non-quinolmentioning
confidence: 89%
“…Previously, we have studied the different capacity of antibiotics to generate fluoquinolone‐resistant mutants in clinical isolates of various Salmonella spp. serotypes (2, 3) and the influence of previous exposition to fluoroquinolones and beta‐lactams on the in vitro activity of other groups of antibiotics (4). In this study, we try to characterize the subpopulations most resistant to fluoroquinolones, produced following repeated exposure to subinhibitory concentrations of different fluoroquinolones and beta‐lactams, by determining the mutant prevention concentration.…”
mentioning
confidence: 99%